Utility of maximum perfusion intensity as an ultrasonographic marker of intraneural blood flow. Issue 1 (4th November 2016) - Borire, Adeniyi A.; Visser, Leo H.; Padua, Luca; Colebatch, James G.; Huynh, William; Simon, Neil G.; Kiernan, Matthew C.; Krishnan, Arun V.
ABSTRACT: We quantified intraneural blood flow (INBF) using perfusion measurement software (PixelFlux), and compared it with the qualitative method of counting blood vessels (vessel score) in a cohort of carpal tunnel syndrome (CTS) patients. Methods: Forty‐seven patients (67 wrists) with a clinical and electrophysiological diagnosis of CTS, and 20 healthy controls (40 wrists) were enrolled. Median nerve ultrasound (US) was performed at the carpal tunnel inlet to measure the cross‐sectional area (CSA) and vessel score. Power Doppler sonograms from nerves with detectable INBF were processed with PixelFlux to obtain the maximum perfusion intensity (MPI). Results: Forty‐nine percent of CTS patients had detectable INBF compared with none in the control group ( P < 0.0001). MPI correlated significantly with vessel score ( r = 0.945, P < 0.0001), CSA ( r = 0.613, P < 0.0001), and electrophysiological severity ( r = 0.440, P < 0.0001). MPI had higher intra‐ or interobserver reliability compared with vessel score (0.95 vs. 0.47). Conclusion: MPI is a better method for quantification of INBF. Muscle Nerve, 2016 Muscle Nerve 55 : 77–83, 2017